PENGEMBANGAN KEILMUAN PROGRAM STUDI JURNALISTIK ISLAM MELALUI MATA KULIAH PEACE JOURNALISM - Asad Isma (Jurnal Dakwah Risalah, 2019)
This study offers a scientific development model for department of islamic journalism  through the approach of peace journalism. Researchers see the importance of peace journalism to be introduced, understood and become the basis of journalistic work of journalists, especially for students. This research uses mixed methods research method that is combining field research, literature and supplemented with online research. The importance of the scientific development of department of islamic journalism through peace journalism can be seen from the increasing need for journalism propositions. The scientific development strategy of the department of islamic journalism at UIN STS Jambi through the Peace Journalism Course starts from curriculum planning, preparation of practice facilities, and hands-on experience-based learning.